2016
DOI: 10.1016/j.jor.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up results of posterior instrumentation without fusion for traumatic thoracic and lumbar spine fractures

Abstract: Posterior instrumentation without fusion is still among the most useful in treatment of traumatic thoracolumbar fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(28 reference statements)
1
6
0
2
Order By: Relevance
“…Initial vertebral body height in all patients and kyphosis in oblique endplates was significantly improved in our study. As reported in other series of traumatic burst fractures, 14,16,19,28 progressive loss of the initial correction of vertebral body height was also noted in our patients, which explained the changes in segmental kyphosis over time; however, similar to these reports, this observation was not associated with symptoms and did not correlate with significant need for reoperation. We believe that the presence of the intact spinal hardware and the adequate load sharing in the reconstructed vertebral body allowed the axial load to be handled; therefore, the small loss of correction was not predictive of poor functional outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Initial vertebral body height in all patients and kyphosis in oblique endplates was significantly improved in our study. As reported in other series of traumatic burst fractures, 14,16,19,28 progressive loss of the initial correction of vertebral body height was also noted in our patients, which explained the changes in segmental kyphosis over time; however, similar to these reports, this observation was not associated with symptoms and did not correlate with significant need for reoperation. We believe that the presence of the intact spinal hardware and the adequate load sharing in the reconstructed vertebral body allowed the axial load to be handled; therefore, the small loss of correction was not predictive of poor functional outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous reports, progressive kyphosis might be inevitable despite fusion. For our study, the residual deformity did not correlate with the symptoms of the patients at their time of follow-up [1,19]. The result showed that the selective fusion procedures achieved comparable clinical and radiographic outcomes with bi-segment fusion groups, which not only validated the selectively fused schemes but also is appropriate for TLF treatment.…”
Section: Discussionmentioning
confidence: 77%
“…Based on previous reports, progressive kyphosis might be inevitable despite fusion. For our study, the residual deformity did not correlate with the symptoms of the patients at their time of follow-up [1,19]. The result showed that the selective fusion procedures achieved comparable clinical and radiographic outcomes with bisegment fusion groups, which not only validated the selectively fused schemes but also is appropriate for TLF treatment.…”
Section: Short-segment Open Instrumentation For Surgically Treated Bumentioning
confidence: 76%